2006
DOI: 10.1007/s11145-005-4644-2
|View full text |Cite
|
Sign up to set email alerts
|

The Contribution of Naming Speed to the Simple View of Reading

Abstract: The purpose of this study was to investigate whether naming speed makes a contribution to the prediction of reading comprehension, after taking into account the product of word decoding and listening comprehension (i.e., the Simple View of Reading; [Gough, P.B. & Tunmer, W.E. (1986). Remedial and Special Education 7, 6-10]), and phonological awareness. In grade 3, word decoding was measured with the Woodcock [(1998). Woodcock Reading Mastery Tests -Revised. Circle Pines, MN: American Guidance Services]. Word I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
147
1
7

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 150 publications
(170 citation statements)
references
References 21 publications
15
147
1
7
Order By: Relevance
“…Furthermore, the phenotypic correlations between word reading and comprehension were higher at initial testing (RD r = 78; control r = .65) than at follow-up (RD r = 54; control r = .48), suggesting that the similarity between them decreases over time. This finding supports results from previous phenotypic studies which suggest that word reading ability is a stronger factor in reading comprehension in younger children (Catts et al, 2005;Curtis, 1980;Johnston & Kirby, 2006;Keenan, Betjemann, & Olson, 2006, submitted).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Furthermore, the phenotypic correlations between word reading and comprehension were higher at initial testing (RD r = 78; control r = .65) than at follow-up (RD r = 54; control r = .48), suggesting that the similarity between them decreases over time. This finding supports results from previous phenotypic studies which suggest that word reading ability is a stronger factor in reading comprehension in younger children (Catts et al, 2005;Curtis, 1980;Johnston & Kirby, 2006;Keenan, Betjemann, & Olson, 2006, submitted).…”
Section: Discussionsupporting
confidence: 90%
“…Keenan, Betjemann, and Olson (2006, submitted) present cross-sectional evidence that within reading comprehension measures, the amount of phenotypic variance accounted for by performance on tests of listening comprehension and word reading tends to shift over time. They demonstrate that in younger children the reading comprehension tasks are more heavily dependent on word reading skill, while in older children the same tasks measure an increasing amount of comprehension skill that is independent of word reading (see also Johnston & Kirby, 2006;Gough et al, 1996;Hoover & Gough, 1990). This suggests that there may be a developmental shift of focus from word reading to comprehension as children get older.…”
Section: Stability Of Relationship Between Measuresmentioning
confidence: 97%
“…Much evidence has provided support for the simple view of reading in several languages (Catts, Adlof, & Ellis Weismer, 2006 ;Johnston & Kirby, 2006 ;Joshi & Aaron, 2000 ;Joshi, Tao, Aaron, & Quiroz, 2012 ;Kendeou, van den Broek, White, & Lynch, 2009 ;Kim, 2015 ;Protopapas, Mousaki, Sideridis, Kotsolakou, & Simos, 2013 ), and showed that oral language skills such as vocabulary and listening comprehension are critical for reading comprehension, and their importance increases as children develop reading skills (Foorman, Koon, Petscher, Mitchell, & Truckenmiller, in press ;Kim & Wagner, 2015 ;Kim, Wagner, & Lopez, 2012 ). Despite its recognized importance, however, what it takes to develop listening comprehension has been nebulous, which is in stark contrast to our understanding about skills that contribute to word reading (see Adams, 1990 ;Bowey, 2005 ;National Early Literacy Panel, 2008 ).…”
Section: Why Listening Comprehension For Reading and Writingmentioning
confidence: 99%
“…Η μορφολογική και συντακτική επίγνωση ως δείκτες πρόβλεψης αναγνωστικών δυσκολιών σε παιδιά πρώτης σχολικής ηλικίας Μερικές από τις γνωστικές διαδικασίες που προτείνονται ως επιπλέον συστατικά στο ΑΜΑ είναι η ευχέρεια ανάγνωσης (Adlof, Catts & Little, 2006), η γρήγορη κατονομασία (Johnston et al, 2006), η φωνολογική επίγνωση (Savage & Wolforth, 2007στο Georgiou et al, 2009) και πρόσφατα και ο έλεγχος της προσοχής (attention control) (Conners, 2009). …”
unclassified
“…Για παράδειγμα, ενώ η ευχέρεια θεωρείται πως συσχετίζεται με την κατανόηση (Fuchs, Fuchs, Hosp & Jenkins, 2001) οι Adlof et al (2006) σε έρευνα με μαθητές των Β΄, Δ΄ τάξεων του δημοτικού και αρχές Γυμνασίου βρήκαν πως η ευχέρεια δεν εξηγούσε επιπλέον διακύμανση της κατανόησης όταν η αποκωδικοποίηση και η προφορική κατανόηση ελέγχονταν. Όσον αφορά την πιθανή επιρροή της γρήγορης κατονομασίας αντικειμένων η κατάσταση περιπλέκεται ακόμα περισσότερο, αφού ορισμένες έρευνες αποκαλύπτουν μια μικρή αλλά σημαντική συνεισφορά στην κατανόηση πέρα από εκείνη που ασκούν η προφορική κατανόηση και η αποκωδικοποίηση (Johnston et al, 2006, Joshi & Aaron, 2000 σε αντίθεση με κάποιες άλλες (Georgiou et al, 2009, Lee et al, 2009). Παρόμοια εικόνα έχουμε και για την επιρροή της ΦΕ (Savage et al, 2007, Georgiou et al, 2009vs.…”
unclassified